Case of Epidermoid Cyst in Parotid Gland in a 23-Year-Old Female Patient Initially Diagnosed as Parotid Tumor: A Rare Case Report - Barsyah Putra, Muhammad Rynaldisatya; Syamun, Rahmens (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Epidermoid cyst is a tumor-like lesion that is generally benign, containing slow-growing keratin and lined by epithelial cells such as epidermis located in the dermis or subcutaneous, where this cyst is very rare in the parotid gland. The incidence of epidermoid cysts in the parotid gland is unclear due to limited reports. Although this lesion is benign, an accurate diagnosis is very important early, so that better management can be carried out. In this case report, a 23-year-old female patient was reported with a lump on the back of the right cheek since 3 years ago. The lump was initially small and slowly enlarged to a fairly large size of about 3 x 4 cm. The lump was the same color as the skin, the punctum was not visible, it was soft to the touch, partially fixed and there was no palpable fluctuation. Ultrasonography examination showed a hypoechoic shadow with a clear boundary in the right parotid area, so that the initial diagnosis was as a right parotid tumor. Initially the plan was for superficial parotidectomy, but switched to parotid cyst excision after the incision in the parotid area showed that the cyst was visible. The removed cyst was examined histopathologically and showed cyst wall tissue with a surface covered with squamous epithelium, the lumen containing a keratin mass, thus confirming that the lesion was an epidermoid cyst. Epidermoid cysts in the parotid gland can be misdiagnosed as parotid tumors due to their similar clinical and radiological manifestations. Accurate identification of clinical and pathological features is essential to differentiate them. Slow growth and ambiguous radiological appearance can lead to misdiagnosis. Complete excision of the parotid cyst is the primary treatment of choice for epidermoid cysts.